1997
DOI: 10.1016/s0002-9394(14)70986-9
|View full text |Cite
|
Sign up to set email alerts
|

Eye Manifestations of Congenital Toxoplasmosis

Abstract: Many children with congenital toxoplasmosis have substantial retinal damage at birth and consequent loss of vision. Nonetheless, vision may be remarkably good in the presence of large macular scars. Active lesions become quiescent with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
3
11

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 32 publications
10
55
3
11
Order By: Relevance
“…However, it should be pointed out that the findings in our study were obtained at the first ophthalmological examination of children up to the age of 12 months and only the paper of Mets et al 14 showed results similar to ours.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, it should be pointed out that the findings in our study were obtained at the first ophthalmological examination of children up to the age of 12 months and only the paper of Mets et al 14 showed results similar to ours.…”
Section: Discussionsupporting
confidence: 72%
“…[8][9][10][11][12][13] Ocular lesions are the most frequent manifestations of congenital toxoplasmosis. 14,15 Prevalence of retinochoroiditis lesions widely vary in literature. 1,10,12,14 These lesions may already be present at birth or they may appear later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A RC foi a alteração ocular mais comum em nossa amostra, o que está de acordo com a literatura 1,2,[8][9][10][11][12] . Estudos que abrangem pacientes maiores de 1 ano apresentam freqüência maior de lesões retinianas, explicado pelo fato de que essas lesões seriam, provavelmente, de aparecimento tardio 5,7 e também pela maior facilidade de execução do exame de fundo de olho (FO) nessa faixa etária.…”
Section: Discussionunclassified
“…Em nosso estudo, o não desenvolvimento de nistagmo nas crianças com catarata, provavelmente se deveu ao fato do exame ter sido realizado nos primeiros meses de vida onde se dá o período crítico para o desenvolvimento do reflexo de fixação 16 . As demais alterações oculares encontradas são todas descritas 8,[10][11][12] .…”
Section: Discussionunclassified